Star Wars. Vol. 2, Operation Starlight - Soule, Charles (Marvel Worldwide, Inc., 2021)
"Commander Ellian Zahra has been tasked by the terrifying Darth Vader with the job of tracking down the remnants of the Rebel Fleet, scattered across the galaxy since the Battle of Hoth. From the bridge of her flagship, the Tarkin's Will, her goal is to eradicate all resistance. But her secret goal is to destroy Leia Organa!"--Provided by publisher.